Preparation, characterization and catalytic behavior of M₀VTₑNbOₓ catalysts prepared by reflux method - Masuri, Shafizah (2012)
MoVTeNbOx catalyst was prepared using reflux method at Mo:V:Te:Nb molar ratio of 1:0.3:0.16:0.12. In order to form the desired structure of orthorhombic M1 phase, three parameters considered were pH, number of washing and niobium source. The first two parameters were observed unsuccessful in forming orthorhombic structure but instead formed tetragonal (V0.07Mo0.93)5O14 and monoclinic TeMo5O16 phases. The monoclinic TeMo5O16 phase was found to become more dominant as the pH of the solution increased. Meanwhile, washing had an effect on the crystallinity of the tetragonal (V0.07Mo0.93)5O14 and monoclinic TeMo5O16 phases. The peaks for both phases were seen to be more intense as the numbers of washing were increased. The desired orthorhombic M1 phase was only formed when using niobium(V) chloride instead of ammonium niobium oxalate as the niobium source. This can be clearly seen by the appearance of the three peaks at 2θ = 6.6°, 7.7° and 8.6°. The catalyst was then further investigated on the effect of calcination period on the orthorhombic formation. Longer calcination period as in this case was 2h, formed better orthorhombic phase with monoclinic TeMo5O16 phase was found diminished. However, the tetragonal (V0.07Mo0.93)5O14 phase in the catalyst was still present. Catalytic testing for propane oxidation into acrylic acid found that catalyst contain less orthorhombic phase showed less activity and selectivity towards the formation of acrylic acid. This was due to the existence of monoclinic TeMo5O16 and tetragonal (V0.07Mo0.93)5O14 phase that hindered the propane to be oxidized to acrylic acid. While for the high orthorhombic content catalyst gave high activity with selectivity towards acrylic acid reached 22%.